Penggunaan media tiktok dan teknik drama voice sebagai strategi terhadap kemampuan mahasiswa dalam berbahasa Inggris - Ni Putu Oka Agustini (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Technological developments can affect the world of education, especially the TikTok application as a medium for learning English, and voice drama techniques are also important for the development and interest in learning English. The purpose of this study was to find out an analysis of the use of Tiktok Media and Voice Drama Techniques on the English-speaking ability of early semester students. This research method is a quantitative method approach where the analysis used is descriptive statistics and hypothesis testing with partial least squares (PLS), with 100 student correspondents. The results of this study based on the above tests show that the Variables of Tiktok Media Use and Drama Voice Techniques are significant.